PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN : Survei Pada Konsumen Pabrik Tahu LA Sariwangi - Santi Febrianti (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
The purpose of the study was to determine, firstly product quality, price perception and purchasing decisions in LA Tahu Sariwangi, secondly the influence of product quality and price perception simultaneously on purchasing decisions in LA Tahu Sariwangi, thirdly the influence of product quality partially on purchasing decisions of LA Tahu Sariwangi and the fourth major influence of price perception partially on purchasing decisions in LA Tahu Sariwangi. The method used in this study is a quantitative method with a survey approach. The results showed that product quality, price perception, and customer purchasing decisions at the LA Sariwangi Tasikmalaya Tofu Factory were in the very good category. There is a simultaneous significant effect of product quality and price perception on purchasing decisions at the LA Sariwangi Tasikmalaya Tofu Factory. There is a partially significant effect of product quality on purchasing decisions at the LA Sariwangi Tasikmalaya Tofu Factory. There is a partially significant effect of price perception on purchasing decisions at the LA Sariwangi Tasikmalaya Tofu Factory.